2013
DOI: 10.3791/50838
|View full text |Cite
|
Sign up to set email alerts
|

Organelle Transport in Cultured <em>Drosophila</em> Cells: S2 Cell Line and Primary Neurons.

Abstract: Drosophila S2 cells plated on a coverslip in the presence of any actin-depolymerizing drug form long unbranched processes filled with uniformly polarized microtubules. Organelles move along these processes by microtubule motors. Easy maintenance, high sensitivity to RNAi-mediated protein knock-down and efficient procedure for creating stable cell lines make Drosophila S2 cells an ideal model system to study cargo transport by live imaging. The results obtained with S2 cells can be further applied to a more phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 28 publications
0
40
0
Order By: Relevance
“…In our search for proteins that mediate dynein-dependent sorting of microtubules in cell processes, we first conducted a candidate-based RNA interference (RNAi) screen in Drosophila S2 cells. S2 cells treated with 2.5 μM of Cytochalasin D (CytoD), an F-actin severing drug, form long microtubule-filled processes (17). Importantly, processes in CytoD treated cells contained abundant cortical actin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our search for proteins that mediate dynein-dependent sorting of microtubules in cell processes, we first conducted a candidate-based RNA interference (RNAi) screen in Drosophila S2 cells. S2 cells treated with 2.5 μM of Cytochalasin D (CytoD), an F-actin severing drug, form long microtubule-filled processes (17). Importantly, processes in CytoD treated cells contained abundant cortical actin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…lens at two different focal planes that are 5-10 μm apart (at the cortex and underneath the cortex, respectively). Images were analyzed in Fiji and DiaTrack 3.04 Pro (73,74), with a maximum particle jump distance of 3.75 μm/s. Velocities were obtained using Analysis > Distribution of Speed (Track-Based) in DiaTrack 3.04 Pro.…”
Section: Methodsmentioning
confidence: 99%
“…Young mated female adults were fattened for ∼48-72 h and dissected in 1× dissecting saline [9.9 mM Hepes (pH 7.5), 137 mM NaCl, 5.4 mM KCl, 0.17 mM NaH 2 PO 4 , 0.22 mM KH 2 PO 4 , 3.3 mM glucose, 43.8 mM sucrose]. Ovaries were placed in lysis buffer on ice [50 mM Tris·HCl (pH 7.4), 150 mM NaCl, 1 mM EDTA, 2 mM MgCl 2 , 1 mM PMSF, 1× CLP (10 μg/mL chymostatin, leupeptin, pepstatin A), 0.5% Triton X-100] and mechanically homogenized using pellet pestles in matching microtubes (74). Ovary homogenates were spun for 10 min at >20,000 × g at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Microtubule sliding is only active in young growing neurons, and becomes undetectable as they mature [15, 16]. Downregulation of microtubule sliding is not caused by inhibition of kinesin-1, since the kinesin-1-dependent organelle transport is still active in mature neurons [9, 15, 16, 36]. We demonstrated that a “mitotic” kinesin Pavarotti (a kinesin-6 family member known in other organisms as MKLP1, CHO1 or KIF20A) is a potent negative regulator of kinesin-1-driven sliding of cytoplasmic microtubules [17], most likely crosslinking anti-parallel microtubules in neurons.…”
Section: Developmental Regulation Of Microtubule Slidingmentioning
confidence: 99%